Information Portals: A New Tool for Teaching Information Literacy Skills. - Debra Kolah; Michael Fosmire (Issues in Science and Technology Librarianship)
Librarians at Rice and Purdue Universities created novel assignments to teach students important information literacy skills. The assignments required the students to use a third-party web site, PageFlakes and NetVibes, respectively, to create a dynamically updated portal to information they needed for their research and class projects. The use of off-the-shelf web 2.0 technology to enable students to discover the latest information in their subject areas of interest provides an engaging, hands-on environment with immediate feedback on the quality of their searching. The authors provide a basic introduction to the use of the 'portal' web site. Then, the results of using this technique, for graduate students in physics in one case and junior/senior level undergraduates in the other, are analyzed, and recommendations for the integration of this type of assignment in other courses are given. [ABSTRACT FROM AUTHOR]